Evaporation of water film in a three-dimensional vertical rectangular channel by laminar mixed convection. (5th February 2018) - Zhang, Liangjun; Huang, Yiye; Wu, Jingyi; Liu, Zhangpeng; Yang, Guang
Highlights: Heat and mass transfer with film evaporation by laminar mixed convection is studied. The mass transfer with film evaporation augments the heat transfer tremendously. The combined buoyancy forces enhance thermo-solutal transfer evidently. Larger Nu and Sh can be observed by increasing aspects ratio. Flow reversal induces a stagnant stage on the Nu and Sh evolution curves. Abstract: This study conducts the numerical analysis of heat and mass transfer with film evaporation by laminar mixed convection in a vertical three-dimensional rectangular channel. Purposely, the study investigates the outcome of inlet dry nitrogen temperature, temperature of wetted wall, Reynolds number and aspect ratio on the heat and mass transfer of thin water film along the isothermal walls. The induced laminar downward flow consists of dry nitrogen and water vapor, which is treated as ideal gases. The thermo-physical properties were connected with the 3-D steady-state and elliptical flow model in view of thin liquid film assumptions. This model's governing equations are solved by implementing the finite volume approach. Also, the velocity pressure fields are connected by the PISO (Pressure Implicit Split Operator) algorithm. The results, which include velocity, temperature and concentration contours, as well as axial evolutions of Nusselt number and Sherwood number were displayed so as to investigate the results for inlet and wall temperatures, Reynolds numbers and aspect ratios. Besides, the influences of buoyancy forces on developing combined thermo-solutal convection are discussed. For the predominated latent heat transfer, the mass transfer with film evaporation augments the heat transfer along the wetted walls tremendously. The different combinations of the opposing thermal and solutal buoyancy forces bring about various flow structures and the flow reversal will occur when Richardson number is large enough.